A Research Publication and Grant Preparation Program for Native American Faculty in STEM: Implementation of the Six R’s Indigenous Framework - Grant, Anne D.; Swan, Katherine; Wu, Ke; Plenty Sweetgrass-She Kills, Ruth; Hill, Salena; Kinch, Amy (Frontiers in Psychology, 2022)
Faculty members in science, technology, engineering, and mathematics (STEM) disciplines are typically expected to pursue grant funding and publish to support their research or teaching agendas. Providing effective professional development programs on grant preparation and management and on research publications is crucial. This study shares the design and implementation of such a program for Native STEM faculty (NAF-STEM) from two tribal colleges and one public, non-tribal, Ph.D. granting institution during a three-year period. The overall development and implementation of the program is centered on the 6 R’s Indigenous framework – Respect, Relationship, Representation, Relevance, Responsibility, and Reciprocity. The role of NAF-STEM and their interactions with the program, as members of the community formed by their participation, impacted the program. Their practices and the program co-emerged over time, each providing structure and meaning for the other. Through such reciprocity, NAF-STEM and the program research team continually refined the program through their mutual engagement. They took on the shared responsibility of the program while they participated in and shaped its practices. The process and results of formative and summative assessment and the impact of COVID-19 on the program are reported. Results of the program offer lessons on the implementation of 6 R’s framework in professional development at institutions of higher education.